Laparoscopic management of hydatid cyst of liver - Changazi, Shabbar Hussain; Rehman, Javaid ur; Bilal, Syed Muhammad; Imran, Muhammad; Ahmad, Qamar Ashfaq; Farooka, Muhammad Waris (Journal of Fatima Jinnah Medical University, 2022)
Background: Hydatic disease is caused by a parasite named Ecchinococcus granulosus. This disease is endemic in Pakistan. The disease mostly affects liver forming cysts. The treatment is mainly surgical which can be performed laparoscopically. This study was thus designed to assess the outcomes of the laparoscopic treatment of hydatid cyst of liver in terms of recovery of patient, complications and recurrence. Subjects and methods: This case series was conducted from March 2015 to December 2020 in Surgical Department of Services Institute of Medical Sciences Lahore. Patients who were planned for laparoscopic surgery for hepatic hydatid cysts (CE2, CE3) were included in the study. Patients who have past history of hepatobiliary surgery, with multiple small cysts or those who has refused for laparoscopic surgery were excluded from study. Demographic data, presenting symptoms, clinicopatholigical findings, duration of surgery, hospital stay and complications were recorded on pre-designed Performa. Results: Total of 42 patients were managed laparoscopically for hydatid liver cyst. The mean age of the patients was 39.42 + 12.04 years. There were 20 (47.62%) male and 22 (52.38%) female patients. Thirty patients (71.43%) were from rural areas. Twenty patients (47.62%) had history of close contacts with dogs or domestic animals. Patients mostly presented with symptoms of pain in right hypochondrium and abdominal mass. Majority of the patients had single hydatid cyst in the liver. Right lobe of the liver was more frequently involved than left lobe. Both lobes were involved in 2 (4.8%) patients. The mean duration of surgery was 76 minutes. No patient developed intra or postoperative anaphylactic shock. Biliary leakage was seen in 4 (9.5%), port site infection in 2 (4.8%) patients and conversion to laparotomy was done in 2 patients (4.8%). The mean hospital stay of patients was 3.41+ 2.82 days. There was no mortality of the patients or recurrence of cyst on 12 week follow up. Conclusion: Laparoscopic surgery for hepatic hydatid cyst is safe and effectual treatment in carefully selected patients. It is a simple technique with lesser postoperative morbidity and potentially decreased risk of complications especially recurrence of disease.